Distinct effects of blood flow and temperature on cutaneous microvascular adaptation - Carter, H.; Spence, Angela; Atkinson, C.; Pugh, C.; Cable, N.T.; Thijssen, D.; Naylor, L.; Green, D. (Lippincott Williams & Wilkins, 2014)
Purpose: We performed two experiments to determine whether cutaneous microvascular adaptations in response to repeated core temperature (Tc) elevation are mediated by increases in skin blood flow (SkBF) and/or skin temperature. Methods: Healthy subjects participated for 8 wk in thrice-weekly bouts of 30-min lower limb heating (40°C). In study 1, both forearms were “clamped” at basal skin temperature throughout each heating bout (n = 9). Study 2 involved identical lower limb heating, with the forearms under ambient conditions (unclamped, n = 10). In both studies, a cuff was inflated around one forearm during the heating bouts to assess the contribution of SkBF and temperature responses. We assessed forearm SkBF responses to both lower limb (systemic reflex) heating and to local heating of the forearm skin, pre- and postintervention.Results: Acutely, lower limb heating increased Tc (study 1, 0.63°C ± 0.15°C; study 2, 0.69°C ± 0.19°C; P < 0.001) and forearm SkBF (study 1, 0.13 ± 0.03 vs 1.52 ± 0.51; study 2, 0.14 ± 0.01 vs 1.17 ± 0.38 cutaneous vascular conductance (CVC); P < 0.001), with skin responses significantly attenuated in the cuffed forearm (P < 0.01). SkBF responses to local heating decreased in study 1 (clamped forearms; week 0 vs week 8, 1.46 ± 0.52 vs 0.99 ± 0.44 CVC; P < 0.05), whereas increases occurred in study 2 (unclamped; week 0 vs week 8, 1.89 ± 0.57 vs 2.27 ± 0.52 CVC; P < 0.05). Cuff placement abolished local adaptations in both studies. Conclusions: Our results indicate that repeated increases in SkBF and skin temperature result in increased skin flux responses to local heating, whereas repeated increases in SkBF in the absence of change in skin temperature induced the opposite response. Repeated increases in Tc induce intrinsic microvascular changes, the nature of which are dependent upon both SkBF and skin temperature.